ANALISIS DISIPLIN KERJA APARATUR SIPIL NEGARA PADA BAGIAN HUKUM DAN ORGANISASI SEKRETARIAT DAERAH KABUPATEN SIGI - Ramlah, Ramlah (Katalogis, 2018)
This study aims to Analyze Work Discipline of State Civil Apparatus In the Legal and Organizational Section of the Regional Secretariat of Sigi Regency. This study uses the Work Discipline theory proposed by Soejono (1997: 67), as an indicator of the discipline of work as well as factors that affect the Work Discipline, including: 1) Timeliness, 2) Using office equipment well, 3) High responsibility, And 4) Obedience to office rules. Research This research is qualitative descriptive research. Informant of the study was determined using Purposive Techniques researcher as much as 6 people. Data analysis in this research is done by stages: 1) Preparation of unit or data editing, 2) Categorization or data grouping, 3) Interpretation or interpretation of data meaning, and 4) Drawing conclusions and research suggestions. The results showed that the Civil State Apparatus Work Discipline in Legal and Organizational Section of Regional Secretariat of Sigi Regency has not run well. This is because of 4 (Four) aspects used to measure the discipline of work are: 1) Timeliness, 2) Using office equipment well, 3) High responsibility, and 4) Obedience to office rules. There are still two aspects that have not gone well, namely aspects of Timeliness and Aspects of Obedience to the rules of the Office. While the other two aspects are running well is the aspect of Using Office Equipment with Good, and Responsibility aspect High.